Edukasi Infeksi Saluran Kemih Pada Ibu PKK Di Desa Temayang, Kerek, Tuban - Fauziansyah, Ahmad; Fahrul Arifin, Mohammad; Ubaidillah Faqih, Moh.; Karyo; Wahdini, Rizqa (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2025)
Health problems are increasing along with the development of diseases. One of them is Urinary Tract Infection (UTI). UTI is a condition where bacteria or microbes grow and multiply in the urinary tract in significant numbers. Generally, UTI is divided into two types: lower UTI and upper UTI. Lower UTI is more common, usually occurring due to bacteria entering through the urethra. Several factors can cause UTI, including age, gender, medication use, catheterization, urinary habits, genital hygiene, and other predisposing factors. In general, women experience UTI episodes more frequently than men, with 20-30% of women experiencing recurrent UTIs. Neonates, adolescent girls, and elderly women are particularly susceptible. The prevalence of UTI in Indonesia is relatively high, with around 180,000 new cases per year. Diagnosis of UTI is based on bacterial count, with Escherichia coli being the most common causative bacteria. Prevention efforts are crucial, especially through health education targeting women. This study aims to educate PKK mothers in Temayang Village about UTI to increase awareness and prevention practices. PKK is a grassroots development movement aimed at achieving family welfare, involving community education and empowerment. The implementation involves a 5-table method with registration, consumption, audience, operator, and MC tables, focusing on UTI education and prevention. Such socialization activities are essential to enhance community knowledge and awareness in preventing and managing health issues like UTIs through education, discussion, and practical tips on clean and healthy living practices.